Soccer penalty takers' uniform colour and pre-penalty kick gaze affect the impressions formed of them by opposing goalkeepers - Greenlees, I.; Leyland, A.; Thelwell, R.; Filby, W. (Journal of Sports Sciences, 2008)
In this study, we examined the impact of soccer players' uniform colour and gaze behaviour on the impressions that are formed of them by opposing goalkeepers. Twelve soccer goalkeepers observed video footage, filmed from between the goalposts to simulate their usual viewpoint, of four players preparing to take a penalty kick. Each of the four players displayed a different combination of gaze (either 90% or 10% with gaze operationalized as looking directly at the camera) and uniform colour (red or white). Goalkeepers rated each player on a series of descriptors (e.g. confidence, composure, assertiveness) and rated their expectancies for successfully saving penalty kicks from that player. Analysis revealed that those penalty takers displaying 90% gaze were perceived to possess positive characteristics to a greater extent than penalty takers displaying 10% gaze. Results also revealed penalty takers wearing red were perceived to possess positive characteristics to a greater extent than those wearing white. Goalkeepers reported higher expectancies of saving penalties from penalty takers displaying 10% gaze and wearing white uniforms than any of the other combinations. Our results therefore support the potential importance of gaze and uniform colour in the formation of impressions and expectancies in sport.